Interprofessional Collaboration Project in Pandemia: reflections by Brazil's National Health System (SUS) professionals about teamwork (Research, Society and Development, 2020)
The "Interprofessional Collaboration Project in Pandemia" aims to present reports from professionals who are working on the front line against the coronavirus, this study aims to report the reflections of health professionals on teamwork in the context of the pandemic through social media. It is a descriptive essay with a qualitative approach, systematized by members of the PET-Saúde / Interprofessionality of Sobral-CE. The information was collected from June 2020 via videos recorded by the professionals who participated in the project, reflecting on the following guiding question: "How has teamwork contributed against COVID-19?" The appreciative analysis of the reports of 10 participants allowed us to perceive a conceptual confusion of the terms interprofessionality and multiprofessionality. However, the importance attributed to teamwork during this pandemic moment was highlighted, in the sense of developing assistance under a comprehensive approach to the patient and his needs, seeking to highlight the importance of each professional in the care process, revealing evidence of a collaborative practice. It is considered that the project contributes to the debate about teamwork in times of pandemic, as well as being an important space for listening and speaking of these health professionals.